2021
DOI: 10.1002/vms3.485
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, expression and structure analysis of key genes in the ovarian steroidogenesis pathway in sheep (Ovis aries)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting that the ovarian steroidogenesis pathway is closely related to ovarian function and development (Gareis et al., 2018), CYP11A1 is a protein‐coding gene, and cholesterol side‐chain cleavage enzyme involved in the biosynthesis of pregnenolone, a unique precursor for all important steroids, such as oestradiol‐17β (E2) (Chung et al., 1997). Movement of cholesterol and further conversion to pregnenolone are the presumed rate‐limiting steps of the steroidogenic pathway (Stocco, 2000), and CYP11A1 occupies a key regulatory part in the biosynthesis of steroids (Hu et al., 2021). STAR is expressed in the ovaries of a variety of animals, encoding steroidogenic acute regulatory protein, mainly overcoming the rate‐limiting transfer of cholesterol from the outer mitochondrial membrane to P450scc (encoded by CYP11A1) located in the cell membrane (Vallee, 2016; Yivgi‐Ohana et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the ovarian steroidogenesis pathway is closely related to ovarian function and development (Gareis et al., 2018), CYP11A1 is a protein‐coding gene, and cholesterol side‐chain cleavage enzyme involved in the biosynthesis of pregnenolone, a unique precursor for all important steroids, such as oestradiol‐17β (E2) (Chung et al., 1997). Movement of cholesterol and further conversion to pregnenolone are the presumed rate‐limiting steps of the steroidogenic pathway (Stocco, 2000), and CYP11A1 occupies a key regulatory part in the biosynthesis of steroids (Hu et al., 2021). STAR is expressed in the ovaries of a variety of animals, encoding steroidogenic acute regulatory protein, mainly overcoming the rate‐limiting transfer of cholesterol from the outer mitochondrial membrane to P450scc (encoded by CYP11A1) located in the cell membrane (Vallee, 2016; Yivgi‐Ohana et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…are the presumed rate-limiting steps of the steroidogenic pathway (Stocco, 2000), and CYP11A1 occupies a key regulatory part in the biosynthesis of steroids (Hu et al, 2021). STAR is expressed in the ovaries of a variety of animals, encoding steroidogenic acute regulatory protein, mainly overcoming the rate-limiting transfer of distinct membrane protein that mediates cholesterol uptake from LDL by endocytosis (Jimenez et al, 2010;Parinaud et al, 1987) and plays central roles in lipoprotein metabolism, and Ldlr −/− female mice are subfertile (Azhar et al, 1998).…”
Section: Movement Of Cholesterol and Further Conversion To Pregnenolonementioning
confidence: 99%
“…This process is promoted by increased expression of CYP11A1 (Chien et al, 2013). It is reported that the increased level of CYP11A1 promotes the development of antral and Graafian follicles (Gershon & Dekel, 2020), and the expression of CYP11A1 in ovarian tissue is far higher in multiparous Small Tail Han sheep than in uniparous Small Tail Han sheep (Hu et al, 2021). This observation is consistent with the results in the current study where we found that CYP11A1 was highly expressed in corpora lutea of polytocous sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of the secondary structure of each protein and its variants was carried out using PredictProtein “ (accessed on 25 October 2022)”. SWISS-MODEL “ (accessed on 02 November 2022)” was used to predict the protein tertiary structure [ 29 ], and a phylogenetic tree was constructed using the neighbor-joining method in MEGA11 software [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%